Glycosynthase with Broad Substrate Specificity – an Efficient Biocatalyst for the Construction of Oligosaccharide Library. Issue 12 (5th March 2013) - Wei, Jinhua; Lv, Xun; Lü, Yang; Yang, Gangzhu; Fu, Lifeng; Yang, Liu; Wang, Jianjun; Gao, Jianhui; Cheng, Shuihong; Duan, Qian; Jin, Cheng; Li, Xuebing
Abstract: A versatile glycosynthase (TnG‐E338A) with strikingly broad substrate scope has been developed from Thermus nonproteolyticus β‐glycosidase (TnG) by using site‐directed mutagenesis. The practical utility of this biocatalyst has been demonstrated by the facile generation of a small library containing various oligosaccharides and a steroidal glycoside (total 25 compounds) in up to 100 % isolated yield. Moreover, an array of eight gluco‐oligosaccharides has been readily synthesized by the enzyme in a one‐pot, parallel reaction, which highlights its potential in the combinatorial construction of a carbohydrate library that will assist glycomic and glycotherapeutic research. Significantly, the enzyme provides a means by which glycosynthase technology may be extended to combinatorial chemistry. Abstract : A versatile glycosynthase (TnG‐E338A) with strikingly broad substrate scope effectively catalyzes the synthesis of an oligosaccharides library (a). The biocatalyst provides a means by which glycosynthase technology may be extended to combinatorial chemistry (b).